ABU AL-HUSAYN AL-BASRI'S USE OF REASON IN 'ILM AL-KALAM AND USUL AL-FIQH - Abdelrahman Eissa, Mohamed Ahmed (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
ABU AL-HUSAYN AL-BASRI'S USE OF REASON IN 'ILM AL-KALAM AND USUL AL-FIQH